Improved Synthesis of MDL 73811 – A Potent AdoMetDC Inhibitor and Anti-Trypanosomal Compound - Brockway, Anthony J.; Cosner, Casey C.; Volkov, Oleg A.; Phillips, Margaret A.; De Brabander, Jef K. (Synthesis, 2016)
An improved synthesis of MDL 73811 – a potent AdoMetDC (S-adenosylmethionine decarboxylase) inhibitor and anti-trypanosomal compound with in vivo activity – has been completed in four steps from commercially available 2′,3′-O-isopropylideneadenosine. Utilization of Mitsunobu chemistry was crucial for the reliable and scalable introduction of the 5′-methylamine moiety, which was problematic using traditional activation/displacement chemistry as previously reported. All reactions in this synthesis were run on gram-scale resulting in a five-fold increase in yield over the original synthesis.
Keywords: nucleosides; drug discovery; Mitsunobu reaction; inhibitors; medicinal chemistry